Acknowledgement to Reviewers 2020 - Gabinete editorial, Revista Portuguesa de Investigação Comportamental e Social (2020)
The high scientific standards maintained by the Portuguese Journal of Behavioral and Social Research in its papers owe much to the effort reviewers, who gave their time freely, and knowledge. Thus, the Editors of the Portuguese Journal of Behavioral and Social Research acknowledge with particular gratitude the following reviewers who have reviewed papers during the period November 2019–November 2020.